The STAR care pathway for patients with pain at 3 months after total knee replacement: a multicentre, pragmatic, randomised, controlled trial. (March 2022) - Wylde, Vikki; Bertram, Wendy; Sanderson, Emily; Noble, Sian; Howells, Nicholas; Peters, Tim J; Beswick, Andrew D; Blom, Ashley W; Moore, Andrew J; Bruce, Julie; Walsh, David A; Eccleston, Christopher; et al.
Summary: Background: Approximately 20% of people experience chronic pain after total knee replacement, but effective treatments are not available. We aimed to evaluate the clinical effectiveness and cost-effectiveness of a new care pathway for chronic pain after total knee replacement. Methods: We did an unmasked, parallel group, pragmatic, superiority, randomised, controlled trial at eight UK National Health Service (NHS) hospitals. People with chronic pain at 3 months after total knee replacement surgery were randomly assigned (2:1) to the Support and Treatment After Replacement (STAR) care pathway plus usual care, or to usual care alone. The STAR intervention aimed to identify underlying causes of chronic pain and enable onward referrals for targeted treatment through a 3-month post-surgery assessment with an extended scope practitioner and telephone follow-up over 12 months. Co-primary outcomes were self-reported pain severity and pain interference in the replaced knee, assessed with the Brief Pain Inventory (BPI) pain severity and interference scales at 12 months (scored 0–10, best to worst) and analysed on an as-randomised basis. Resource use, collected from electronic hospital records and participants, was valued with UK reference costs. Quality-adjusted life-years (QALYs) were calculated from EQ-5D-5L responses. This trial is registered with ISRCTN, ISRCTN92545361. Findings: Between Sept 6, 2016, and May 31, 2019, 363 participants were randomly assigned to receive the intervention plus usual care (n=242) or to receive usual care alone (n=121). Participants had a median age of 67 years (IQR 61 to 73), 217 (60%) of 363 were female, and 335 (92%) were White. 313 (86%) patients provided follow-up data at 12 months after randomisation (213 assigned to the intervention plus usual care and 100 assigned to usual care alone). At 12 months, the mean between-group difference in the BPI severity score was −0·65 (95% CI −1·17 to −0·13; p=0·014) and the mean between-group difference in the BPI interference score was −0·68 (−1·29 to −0·08; p=0·026), both favouring the intervention. From an NHS and personal social services perspective, the intervention was cost-effective (greater improvement with lower cost), with an incremental net monetary benefit of £1256 (95% CI 164 to 2348) at £20 000 per QALY threshold. One adverse reaction of participant distress was reported in the intervention group. Interpretation: STAR is a clinically effective and cost-effective intervention to improve pain outcomes over 1 year for people with chronic pain at 3 months after total knee replacement surgery. Funding: National Institute for Health Research.